Evolution of the Southern Annular Mode during the past millennium - Abram, NJ; Mulvaney, R; Vimeux, F; Phipps, SJ; Turner, J; England, MH (2014)
The Southern Annular Mode (SAM) is the primary pattern of climate variability in the Southern Hemisphere, influencing latitudinal rainfall distribution and temperatures from the subtropics to Antarctica. The positive summer trend in the SAM over recent decades is widely attributed to stratospheric ozone depletion; however, the brevity of observational records from Antarctica-one of the core zones that defines SAM variability-limits our understanding of long-term SAM behaviour. Here we reconstruct annual mean changes in the SAM since AD 1000 using, for the first time, proxy records that encompass the full mid-latitude to polar domain across the Drake Passage sector. We find that the SAM has undergone a progressive shift towards its positive phase since the fifteenth century, causing cooling of the main Antarctic continent at the same time that the Antarctic Peninsula has warmed. The positive trend in the SAM since ~AD 1940 is reproduced by multimodel climate simulations forced with rising greenhouse gas levels and later ozone depletion, and the long-term average SAM index is now at its highest level for at least the past 1,000 years. Reconstructed SAM trends before the twentieth century are more prominent than those in radiative-forcing climate experiments and may be associated with a teleconnected response to tropical Pacific climate. Our findings imply that predictions of further greenhouse-driven increases in the SAM over the coming century also need to account for the possibility of opposing effects from tropical Pacific climate changes.